The performance analysis of extended kalman filter on radar target tracking - Avci, Engin; Turkoglu, Ibrahim; Poyraz, Mustafa (My University, 2006)
In this study, the tracking performance of radar target tracking process by using extended Kalman filter is analyzed. For this purpose, the obtained real radar datasets are used for extraction of the target motion model, observation model, processing noise and measurement noise equations based on experimental study respectively. Extended Kalman filter algorithm is applied to the equations and the results of target tracking are evaluated. The evaluation process is done for some processing and measurement noise level and successful results are obtained.
Keywords: Extended Kalman filter (EKF); Radar; Target tracking